- #1

susyq232

- 2

- 0

Vector A has a magnitude of 17 (in some unspecified units) and makes an angle of 27° with the x axis, and a vector B has a length of 26 and makes an angle of 75° with the x axis. Find the components of the vector in the following.

(a) C = A + B

( , )

(b) C = A - B

( , )

(c) C = A + 4B

( , )

(d) C= -A-7B

( , )

I did the entire problem and submitted it to webassign and it came back as wrong.

what i first did was draw vector a from the origin pointing up diagnally between the x and y axis. then from the tip of that i connected the tail of b pointing in also up diagnally between the x and y just with a sharper angle ( so the a is shaped like the bottwem half of the symbol '>' and then i added a '/' symbol to the tip)

so that's my picture. then i connected the end of A and the tip of B with a vector C. i then solved all the lengths of the smaller triangles then added ax and bx and ay and by to get the entire c vector's triangle for a+b = c. then i did ax-bx and ay-by to fnd a-b=c and so on.

my answers i got for the problem that webassign says is wrong:

(a) c= a + b

(39,56)

(b) c= a-b

(-7,-25)

(c) c= a + b4

(102,139)

(d) c= -a -7b

(-168,-237)

(a) C = A + B

( , )

(b) C = A - B

( , )

(c) C = A + 4B

( , )

(d) C= -A-7B

( , )

I did the entire problem and submitted it to webassign and it came back as wrong.

what i first did was draw vector a from the origin pointing up diagnally between the x and y axis. then from the tip of that i connected the tail of b pointing in also up diagnally between the x and y just with a sharper angle ( so the a is shaped like the bottwem half of the symbol '>' and then i added a '/' symbol to the tip)

so that's my picture. then i connected the end of A and the tip of B with a vector C. i then solved all the lengths of the smaller triangles then added ax and bx and ay and by to get the entire c vector's triangle for a+b = c. then i did ax-bx and ay-by to fnd a-b=c and so on.

my answers i got for the problem that webassign says is wrong:

(a) c= a + b

(39,56)

(b) c= a-b

(-7,-25)

(c) c= a + b4

(102,139)

(d) c= -a -7b

(-168,-237)

Last edited: